Strategies to improve the retention of certificate foundation program students into diploma programs at Unifield International College / Nur Iylia Syafiqah Abdul Malik, Nor Shazreen Mazlan and Noor Humaira Mohamad - Abdul Malik, Nur Iylia Syafiqah; Mazlan, Nor Shazreen; Mohamad, Noor Humaira (2016)
The higher education industry is complex and diverse. Higher education has become a vibrant business in Malaysia and it is of paramount importance to cultivate the creative and innovative intellectual human capitals that are needed for the future growth of the economy. With the rising population of high school leavers and rising costs of providing public higher education, the Malaysia government encourages the establishment of private higher education in Malaysia. As a private higher education institution, UIC need to ensure the number of students' enrolment is increasing from year to year in order to sustain in the industry. Therefore, the main objective of this study is to perform a situational analysis of UIC as a university of choice among students in Melaka. Besides that, this study would like to recommend the best strategies to be implemented. The respondents are 260 CFP students who need to answer a set of questionnaires. By using SPSS, the result show that all independent variables and dependent variable are positively correlated and social connectedness is the main factor influencing student retention, this study had used TOWS Matrix as a strategic tool to recommend on strategies to be implemented.